Stability of orthodontic anchoring devices: a narrative review - Magdalena Enache; Dana Festila; Cristina Ciubotariu; Samer Ghazawi; Olimpia Bunta; Mihaela Pastrav; Cristian Olteanu; Mircea Ghergie (Romanian Journal of Stomatology)
Background and objectives. Temporary anchoring devices (TADs) are essential for controlling unwanted reactive movements in teeth because orthodontic treatments require effective anchorage to control tooth movement. The goal of this systematic review is to collect information on the advantages, disadvantages, and applications of TADs in orthodontic treatment by addressing the variables affecting their stability and efficacy. Materials and methods. Our review is a non-Cochrane review, following the PICO format for selection criteria, analyzed studies published between 2011 and 2021. The review focused on systematic reviews, meta-analyses, RCTs, case control, and cohort studies in English, extracted from PubMed and Google Scholar databases. A total of 123 papers were assessed, with 39 included for review. Results. The review found that TAD stability is highly influenced by micro-implant design, operator experience, placement technique, bone morphology and histology, and patient variables (such as age and sex). Notably, the quality and amount of bone, the length and diameter of the implant, and the surgical method all played a significant role in achieving primary stability. Although loosening and discomfort are possible side effects, TADs have been demonstrated to provide reliable and effective anchoring during orthodontic treatment. Conclusions. Greater treatment efficacy and patient comfort are made possible by the significant advancement in orthodontic anchoring that TADs represent. The performance of TADs is largely dependent on variables like operator experience, micro-screw size, and bone quality. The mandibular site presented a higher risk of loosening, although patient factors such as age and sex did not significantly affect the loosening rate. This review emphasizes how important it is to take these factors into account in order to maximize TAD stability and, consequently, therapeutic results.